Integration of Hadith Studies with the Development of Pancasila Development - Rohmadi Rohmadi; Ahmad Mohammad Tidjani; Abdul Kirom (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
Hadith studies are a key Islamic discipline, serving as a source of normative teachings after the Quran. The hadith of the Prophet Muhammad (peace be upon him) not only regulate aspects of worship but also provide comprehensive guidance on social ethics, leadership, justice, and societal responsibility. In Indonesia, Pancasila, as the foundation of the state and national ideology, serves as the primary foundation for national development, encompassing political, social, cultural, and educational aspects. This article aims to examine the integration of hadith studies with the development of Pancasila in an effort to strengthen the internalization of national values ​​based on Islamic morals and ethics. This study uses a qualitative approach with library research methods, analyzing hadith texts, the Quran, and scholarly journals discussing Pancasila, character education, and national development. The results indicate substantial alignment between the values ​​contained in the hadith and the principles of Pancasila, such as monotheism, humanity, unity, deliberation, and social justice. The integration of hadith studies in the development of Pancasila development has the potential to strengthen the moral and spiritual dimensions of national development, particularly in the context of Islamic education and community development.